Endothelial Protein C Receptor: A Multifunctional Mediator in the Pathophysiology of Rheumatoid Arthritis - Meilang Xue; Lyn March (Cells)
The endothelial protein C receptor (EPCR) is gaining recognition for its diverse functions that extend beyond its traditional role in the protein C anticoagulant pathway. This comprehensive review examines how EPCR contributes to the pathophysiology of rheumatoid arthritis (RA), an autoimmune disorder characterized by persistent inflammation and joint destruction. We explore how EPCR influences inflammatory responses and the coagulation cascade, affects endothelial function and vascular integrity, and regulates the characteristics of synovial fibroblasts in the context of RA. Furthermore, the review highlights the mechanisms by which EPCR affects disease progression, its potential use as a biomarker for disease activity, and the therapeutic implications of targeting EPCR in the treatment of RA. By synthesizing current research findings, this review aims to provide a detailed understanding of EPCR’s role in RA, offering insights into innovative diagnostic and therapeutic strategies that could improve patient outcomes.